Black Lambs and Grey Falcons: Women Travelling in the Balkans, eds. John B. Allcock and Antonia Young - Lazarević Radak, Sanja (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Black Lambs and Grey Falcons: Women Travelling in the Balkans. Ed. by John B. Allcock and Antonia Young. New York, Oxford: Berghahn Books, 2000, pp. 308.